The Effectiveness of Problem Based Learning (PBL) and Audiovisual Media Towards Enhancement of Mathematics Learning Outcomes at Grade IV SDN 07 Tiumang - Miyato Miyato (The Future of Education Journal, 2022)
The problem behind this research is related to learning methods in mathematics lessons that are carried out in the form of lectures and homework assignments so that it has an impact on students' lack of interest in learning which is marked by students' lack of enthusiasm in mathematics and less active in class which causes low student learning outcomes. . The purpose of this research is to improve students' mathematics learning outcomes through collaborative problem based learning (pbl) methods and audiovisual media that are adapted to process standards. This research was conducted with class action steps consisting of 2 cycles with each meeting 3 times. The subjects of this study were the fourth grade students of SDN 07 Tiumang with a total of 41 students. The assessment instrument uses a written test and criteria in the form of limited description questions and observation sheets. The results showed an increase in student learning outcomes in mathematics as seen from the class average score. The value before intervention was 68.7. The value in the first cycle increased to 78.5 and increased again in the second cycle to 87.8. The student's completeness score before the intervention was 42.9%. Completeness in the first cycle was 76.9% and increased again in the second cycle to 90.47%. The conclusion of this study is that there is an effect of collaborative problem based learning (pbl) methods and audiovisual media adapted to process standards on student learning outcomes in mathematics. Suggestions for this research are that teachers are expected to be able to apply this method to increase student activity and learning outcomes in mathematics, and can add work in the school library, can complement the weaknesses of previous learning and find new things, namely collaboration problem based learning (pbl) methods and audiovisual media